As novas tendências de Concept Art : a concepção tridimensional - Voloshchuk, Nazariy, 1992- (2018)
This investigation related to de use of the new technologies, applied to the creative process that involves the elaboration and graphic development of concept art. The present study aims to present two different methodologies through the use of mixed tools based on current techniques of the authors specialized in projects directed to the entertainment industry, designated by Concept Art. The basic structure of this work corresponds to the theoretical aspect that describes the relevance of Concept Art in pre-production and aims to clarify the author's divergence regarding the new trends of three-dimensional conceptualization. At the same time, the practical side is presented, which focuses on the demonstrative component of the constructive methods of the author's two-dimensional projects. In the investigation of the origin of the Concept Art field, it was considered appropriate to briefly introduce the panorama of this aspect in cinema and video games, as the "medium" that aims to determine the visual language of the project, regardless of the method as the concept is developed. For this reason, based on the comparison of the most archaic techniques, the new methodological tendencies of the various authors were mentioned, which highlight the innovation in this field of activities. The most practical approach of this work is to demonstrate the stepwise process of the current methods of commercial production. In each phase, the references and definition of the author's methods are related, being equivalently accompanied, at the end of each stage, by the practical demonstration of the author's three-dimensional projects